2019
DOI: 10.22296/2317-1529.2019v21n1p137
|View full text |Cite
|
Sign up to set email alerts
|

Estratificação Sócio-Ocupacional e Segregação Espacial na Metrópole de São Paulo nos Anos 2000 | Socio-occupational stratification and spatial segregation in the São Paulo Metropolis in the 2000s

Abstract: O presente artigo faz um estudo empírico das alterações na distribuição espacial e no padrão de segregação sócio-espacial das classes sociais na Região Metropolitana de São Paulo (RMSP) nos anos 2000, utilizando a metodologia desenvolvida pelo Observatório das Metrópoles para a análise da estratificação sócio-ocupacional. Serão empregadas ferramentas estatísticas espaciais, com destaque para o Índice de Moran, calculado para as Áreas de Ponderação da RMSP nos anos de 2000 e 2010, para análise espacial dos padr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…According to Musterd et al (2015), previous studies on socio-economic residential segregation in the United States of America and European countries reveal that higher socio-economic groups are generally more segregated than lower socio-economic ones. Such patterns have also been found in cities of Latin America (Agostini et al 2016;Becceneri et al 2019;Molinatti 2013;Sabatini et al 2009, among others). The If we analyze the variations between 1991 and 2010, taking into account the economic fluctuations that occurred during the period analyzed, it can be observed that the levels of socio-economic residential segregation showed a little variation for the extreme socio-economic groups, defined according to the highest educational level attained.…”
Section: Socio-economic Segregation According To Global Indicessupporting
confidence: 59%
“…According to Musterd et al (2015), previous studies on socio-economic residential segregation in the United States of America and European countries reveal that higher socio-economic groups are generally more segregated than lower socio-economic ones. Such patterns have also been found in cities of Latin America (Agostini et al 2016;Becceneri et al 2019;Molinatti 2013;Sabatini et al 2009, among others). The If we analyze the variations between 1991 and 2010, taking into account the economic fluctuations that occurred during the period analyzed, it can be observed that the levels of socio-economic residential segregation showed a little variation for the extreme socio-economic groups, defined according to the highest educational level attained.…”
Section: Socio-economic Segregation According To Global Indicessupporting
confidence: 59%
“…The capital is the most populated city in Brazil, with 12.3 million inhabitants. In the SPMA, the other cities with more inhabitants are Guarulhos (1.4 million), The capital and its nearest cities concentrate most of the job opportunities, public facilities and services, universities, museums, and entertainment options [32]. Thus, there is huge daily commuting to the capital downtown and its surrounding neighboring.…”
Section: São Paulo Metropolitan Areamentioning
confidence: 99%